GEOGRAPHICAL FEATURES OF POVERTY AND FORMATION OF MIDDLE CLASS IN UKRAINE - Перегуда, Юлія (Human Geography Journal, 2015)
The article examines the social and geographical aspects of poverty and the middle class in Ukraine. The essence of the concepts of "poverty" and "middle class." Defined social and geographical aspects of the study of the middle class in Ukraine and government policy on poverty reduction. The necessity of implementation of government measures aimed at creating an appropriate legal framework and economic environment for poverty eradication. The formation of future strong middle class, you must connect with prospects of poverty reduction programs in Ukraine.